Edukasi Kesehatan : Kontrasepsi Pada Pasangan Usia Subur (PUS) - Aisyiyah, Nani; Sari, Dewi Nawang; Herlina, Lina; Siswani, Sri; Ekaputri, Della Eriana; Waluyo, Ari; Sangadji, Ismail (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2026)
The use of contraception among couples of reproductive age is an important effort to regulate birth spacing and the number of children; however, many couples still have limited knowledge regarding the types, effectiveness, and side effects of contraceptive methods. This condition causes most couples to continue using hormonal contraception for long periods despite experiencing complaints such as weight gain, menstrual disorders, headaches, changes in libido, and increased blood pressure. This community service activity aimed to improve the knowledge and understanding of couples of reproductive age regarding hormonal and non-hormonal contraception through health education activities. The method used was counseling by delivering educational materials using PowerPoint media and interactive discussions. The target participants were couples of reproductive age in RT 01 RW 04, Bambu Apus Subdistrict, Cipayung District, East Jakarta, with a total of 18 women of reproductive age. The results showed that participants were very enthusiastic in attending the education sessions, actively participated in question-and-answer discussions, and experienced an increase in knowledge regarding types of contraception, side effects, and their management. Contraceptive health education is expected to assist couples of reproductive age in choosing appropriate contraceptive methods, reducing side effects, and improving reproductive health status